The 50 years of the World Heritage Convention in Spain: implementation, effects, and challenges - Mónica Luengo; Celia Martínez; Xavier Casanovas; Maider Maraña; Jordi Tresserras; Cristina Lafuente (Ochrona Dziedzictwa Kulturowego)
Due to the diversity of characteristics and the high number of World Heritage sites (49) inscribed by Spain, this country and its ICOMOS National Committee have a long experience in the application of the World Heritage Convention throughout these 50 years. The World Heritage Working Group of the Spanish National Committee of ICOMOS has therefore carried out an analysis of these sites, their history and evolution, typology, and state of conservation with the final goal of assessing their current heritage situation and the contribution of the Convention to the conservation of the Spanish natural and cultural heritage. We also aim to reflect on how Spain has contributed to the World Heritage Convention during these five decades and about the most important challenges that our country needs to confront in order to continue complying with the spirit of the Convention and the principles of its Operational Guidelines.